2018
DOI: 10.1371/journal.pone.0205977
|View full text |Cite
|
Sign up to set email alerts
|

Under five mortality patterns and associated maternal risk factors in sub-Saharan Africa: A multi-country analysis

Abstract: BackgroundUnder-5 mortality rate in the sub-Saharan region has remained unabated. Worse still, information on the regional trend and associated determinants are not readily available. Knowledge of the trend and determinants of under-5 mortality are essential for effective design of intervention programmes that will enhance their survival. We aimed to examine the mortality patterns in under-5 children and maternal factors associated with under-5 deaths.MethodsDemographic and Health Survey (DHS) data from five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
111
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(153 citation statements)
references
References 22 publications
40
111
2
Order By: Relevance
“…Average child size at birth ((0.68), (0.51, 0.90) prevent under-ve daughters mortality than very large daughters at birth. This agreed with a study derived from the 2016 EDHS data (5,30,34).Unplanned birth ((1.70), (1.03, 2.81) increase the likelihood of sons death than planned births. This contradict with a study that reported a preventive association (26).…”
Section: Discussionsupporting
confidence: 89%
“…Average child size at birth ((0.68), (0.51, 0.90) prevent under-ve daughters mortality than very large daughters at birth. This agreed with a study derived from the 2016 EDHS data (5,30,34).Unplanned birth ((1.70), (1.03, 2.81) increase the likelihood of sons death than planned births. This contradict with a study that reported a preventive association (26).…”
Section: Discussionsupporting
confidence: 89%
“…2 Sepsis-related deaths in SSA reflect underlying political, poverty, health inequity and health system challenges across Africa. 5 These challenges affect preventative and public health efforts to prevent sepsis and limit prompt and effective recognition and treatment of sepsis to prevent mortality. The challenges include access to clean water and sanitation, vaccination and provision of primary care in addition to access to antimicrobial agents and strategies for their stewardship.…”
Section: Introductionmentioning
confidence: 99%
“…The determinants of child and under-5 mortalities are highly correlated with socioeconomic, demographic, and behavioral factors of households, health seeking behavior of mothers, and environmental factors. Several studies have investigated that maternal age and education be found to be strongly correlated with child morality [9,[13][14][15][16][17][18][19]. Level of education is inversely associated with child mortality children of educated mothers having better survival than children of noneducated mothers [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Other determinants of child mortality may include place of residency [14,19,[25][26][27], family size and parity [9,[21][22][23], birth order, birth intervals [19,24], water source [21,26], and toilet facility [16,21]. Bearing many children increases the risk of maternal mortality and the death of the newborns as well [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation